Mitigasi Resiko: Studi Kasus Keikutsertaan Petani dalam Program Asuransi Usahatani Padi - Rizky Yanuarti; Indah Ibanah (Jember University Press, 2023)
Sustainability of agricultural sector, especially within rice commodity which still becomes the main food for most of Indonesian’s, needs attention. Rice farming faces variety of risks and uncertainty conditions such as floods, droughts, and pest attacks. Global climate change in recent years has exacerbated the effects of natural hazards. Agricultural insurance become one solution to overcome farming risk. But in fact, farmers participation level still low. The purpose of this study is to identify the factors that influence farmers' decisions to participate in Rice Farming Insurance (AUTP) as a government-facilitated risk mitigation measure. The study was conducted in Wuluhan Sub-District, Jember Regency with total sample of 130 farmers who were randomly selected. Primary data was collected through interviews by filling out a structured questionnaire. The collected data was processed using logistic regression analysis to determine factors that significantly influence farmers' decisions. The results showed that the risk aversion level, age, experience, land area and crop failure occurence due to pests attack had significance wald test value (partial test) of 0.000; 0.098; 0.022; 0.002; and 0.024. So it can be said that the five variables significantly influence the farmers' decision to participate in AUTP at the confidence level of 95% and 90%.